2022
DOI: 10.1186/s12871-022-01852-w
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, safety, and teamwork: a qualitative study on the experiences of anaesthesiologists and nurse anaesthetists working in the preanaesthesia assessment clinic

Abstract: Background The preanaesthesia assessment clinic (PAC) has been shown to contribute to safe anaesthesia assessment in hospitals. In the PAC, patients are assessed with an interview and can also ask relevant questions about anaesthesia. The intention is to ensure that patients are comprehensively prepared for the surgery and hospital stay. Although earlier studies have assessed the effects of PAC, attitudes and satisfaction of the healthcare personnel working in PAC remain unknown. Thus, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Firstly, this highlights the importance of balancing individual goals with group responsibilities. This balance is crucial for maintaining a work environment that is both cooperative and efficient, creating an optimal learning environment [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, this highlights the importance of balancing individual goals with group responsibilities. This balance is crucial for maintaining a work environment that is both cooperative and efficient, creating an optimal learning environment [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…If it doesn't happen in an organized context, it tends to happen on the sidelines in a non-constructive manner. " (Interview 13, line [20][21][22][23][24][25][26][27] Here, all aspects of learning are considered in a mature, self-reflective, critical, and confident manner. "So, I've noticed with some of my colleagues, at least, that they have sort of evolved and started to see things in a different way.…”
Section: Interviewee Quotementioning
confidence: 99%
“…A common theme for the anaesthesia personnel was that they learned a lot about different medications and diseases, which they considered important knowledge [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in the past that anesthesiologist-driven and multidisciplinary preoperative clinics can provide value in reducing patient anxiety, costs, length of stay, and mortality [33,34,35 ▪ ]. A recent study by Beckerleg et al [36] showed that preoperative medical consultation was associated with an increase in adverse postoperative outcomes, and increase in resource utilization.…”
Section: How Can We Prepare Patients For Nonoperating Room Anesthesia...mentioning
confidence: 99%